2019
DOI: 10.1148/radiol.2019190425
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mammography versus Breast Tomosynthesis: Impact of Breast Density on Diagnostic Performance in Population-based Screening

Abstract: he sensitivity of digital mammography (DM) is lower in women with dense breasts than in those with lower breast density (1). Breast density is also associated with higher false-positive rates and recall rates (2) due to superposition of normal glandular tissue that can mimic cancer. The woman's age has an impact on mammography screening as breast density decreases (3) and cancer incidence increases. The distribution of cancers shifts toward less-aggressive slower-growing cancers with increasing age (4). It has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 33 publications
(46 reference statements)
5
39
0
Order By: Relevance
“…Therefore, they will represent women with cancers, benign findings or women that are difficult to assess. This group has a higher breast density on average than all women included in OTST (155).…”
Section: Reader Study (Paper I and Ii)mentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, they will represent women with cancers, benign findings or women that are difficult to assess. This group has a higher breast density on average than all women included in OTST (155).…”
Section: Reader Study (Paper I and Ii)mentioning
confidence: 84%
“…This indicates that the radiologists were more likely to classify breasts as dense and extremely dense in the reader study than in a screening setting. (155). As the confidence intervals overlap, the difference was not significant.…”
Section: Comparison Of Density Assessment In the Reader Study And Otstmentioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, let’s consider the scenario of replacing digital mammography as the screening imaging modality for a higher-performing technique, e.g., digital breast tomosynthesis (DBT). Over a number of prospective screening trials, DBT has been found to result in higher detection performance, but with a doubling of the reading time [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ]. Therefore, introduction of DBT-based screening, which has already taken place in the US, where screening is institution-based [ 30 ], is also of intense interest in countries where screening is regional- or national-program based.…”
Section: Achieving Stand-alone Computer Interpretation: When Is It Fementioning
confidence: 99%
“…For example, the DBT increases the cancer detection rate but is less effective for women with extremely dense breasts (Vourtsis and Berg, 2019). A recent study reported that DBT enabled the detection of more cancers in all density and age groups compared with DM, especially cancers classified as spiculated masses and architectural distortions (Osteras et al, 2019). DBT and DM screening increased the detection rate of histologically favorable tumors compared with that attained by DM screening (Hofvind et al, 2018).…”
Section: Introductionmentioning
confidence: 99%